PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. BUSSAN AUTO FINANCE CABANG PAYAKUMBUH - Romi Susanto (Jurnal Bina Bangsa Ekonomika, 2024)
Theoretically the factors that affect employee performance are work discipline, employee skill level, and innovative behavior. Employee performance in the organization is strongly influenced by employee discipline. If among employees do not pay attention to work discipline, then the performance possibilities of employees in an organization may decrease. Because to obtain good performance is very necessary discipline employees in an organization. The purpose of this study to determine how far the influence of work discipline on the performance of employees of PT. Bussan Auto Finance Branch Payakumbuh. This research is kind of reserch field research and using quantitative approach. Quantitative research is a study that sees a reality as a single thing, observed, and can be dipragmentasikan so that from the existing problems can analyze and meprediksi a problem based on a number of variables. While the sample in this study is all employees of PT. Bussan Auto Finance Payakumbuh branch as many as 35 people. So the researchers spread the questionnaire as many as 35 respondents. Sampling using incidenta sampling technique. The analysis method used is multiple linear regression method and using t-test with significance level a = 5%. where to determine t table can be seen in the statistical table on the significance of 0.05 / 2 = 0.025 with degrees of freedom df = N-2 or 35-2 = 33. Results obtained for t table is 2.035 From the test results can be known where the value of t arithmetic of 7,866